Efektivitas Sighat Taklik Talak Dalam Perkawinan Islam Di Indonesia - K N Sofyan Hasan; Ahmaturrahman Ahmaturrahman; Sri Turatmiyah (Faculty of Law, Universitas Pattimura, 2022)
The effectiveness of the Sighat Taklik Talak in Islamic marriage law in Indonesia, until now from the aspect of the implementation of this Sighat Taklik Talak pronunciation, after the Ijab Kabul is held in the marriage walimah, is always spoken by the husband who is heard by all the marriage aqdun assemblies. It was even signed by the bride and groom and the witnesses, so this Sighat Taklik Talak has legal consequences. However, in the implementation of taklik talak as the causes of divorce, it can be said that it is rarely used or even none at all who applies for divorce through the path or means of violating sighat taklik talak, and because there is no request from one of the parties to divorce, then the judge cannot use sighat taklik talak as the reason for the divorce because the judge is passive.